The Influence of Intellectual Capital on Firm Value with Institutional Ownership as a Moderation Variable - Dewi, Anindya Nurmalita (Devotion : Journal of Research and Community Service, 2023)
The benchmark for the success of a company can be seen in the resources that support and support the company's activities. This is expected to be able to improve financial performance from time to time, so that the company is able to achieve targets to maintain the company's survival. Therefore, the purpose of this study is to examine and analyze how Intellectual Capital (IC) affects Firm Value, examines and analyzes how Institutional Ownership influences Intellectual Capital (IC) to Firm Value, examines and analyzes how Institutional Ownership moderates the influence of Intellectual Capital (IC) on company value. For this research, the population is all conventional general banking listed on the Indonesia Stock Exchange (IDX) from 2017 – 2021. The sample of this study uses banking companies that have been listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2021. The conclusion in this study is: Intellectual Capital (VAIC) has a positive effect on Firm Value (TOBINS_Q), Institutional Ownership (KI) has a positive effect on Firm Value (TOBINS_Q), Institutional Ownership can moderate the effect of Intellectual Capital on Firm Value.